Reproducibility of neutron activated Sm-153 oral dose formulations intended for human administration - Yeong, C.H.; Blackshaw, P.E.; Ng, K.H.; Abdullah, B.J.J.; Blaauw, M.; Dansereau, R.J.; Perkins, A.C. (Elsevier, 2011)
Neutron activation of Sm-152 offers a method of radiolabeling for the in vivo study of oral dose formulations by gamma scintigraphy. Reproducibility measurements are needed to ensure the robustness of clinical studies. 204 enteric-coated guaifenesin core tablets (10 mg of Sm(2)O(3)) were irradiated by thermal neutrons to achieve 1 MBq at 48 h. Administered activities were 0.86 +/- 0.03 MBq. Good reproducibility (CV=3.5) was observed over 24 weeks ensuring that volunteer doses were within the dose reference level of 0.8 mSv.